The European Social Model: Coping with the challenges of diversity - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 2002)
European integration has created a constitutional asymmetry between policies promoting market efficiencies and policies promoting social protection and equality. National welfare states are legally and economically constrained by European rules of economic integration, liberalization, and competition law, whereas efforts to adopt European social policies are politically impeded by the diversity of national welfare states, differing not only in levels of economic development and hence in their ability to pay for social transfers and services but, even more significantly, in their normative aspirations and institutional structures. In response, the Open Method of Coordination is now applied being in the social-policy field. It leaves effective policy choices at the national level, but tries to improve these through promoting common objectives and common indicators and through comparative evaluations of national policy performance. These efforts are useful but cannot overcome the constitutional asymmetry. Hence there is reason to search for solutions which must have the character of European law in order to establish constitutional parity with the rules of European economic integration, but which also must be sufficiently differentiated to accommodate the existing diversity of national welfare regimes. The article discusses two such options, Closer Cooperation and a combination of differentiated framework directives with the Open Method of Coordination. – – Die Europäische Integration hat eine konstitutionelle Asymmetrie zwischen marktschaffender Politik und soziale Sicherheit und Gleichheit fördernder Politik erzeugt. Sozialstaatliche Politik auf der nationalen Ebene wird beschränkt durch Marktintegration, Liberalisierung und das europäische Wettbewerbsrecht. Zugleich scheitert aber eine einheitliche europäische Sozialpolitik an Unterschieden in der wirtschaftlichen Leistungsfähigkeit noch mehr an der Verschiedenartigkeit der normativen Erwartungen und der institutionellen Strukturen der nationalen Sozialsysteme. Als Antwort darauf wird nun die Offene Methode der Koordinierung in der Sozialpolitik angewandt. Die Methode belässt die Wahl der Policy auf nationaler Ebene, versucht aber gleichzeitig, diese durch die Definition gemeinsamer Ziele und Indikatoren sowie durch Erfolgsvergleiche zu verbessern. Diese Bemühungen sind zwar nützlich, können jedoch die konstitutionelle Asymmetrie nicht beseitigen. Es lohnt sich deshalb, nach Lösungen zu suchen, die den Status europäischen Rechts haben, um so konstitutionellen Gleichrang mit dem europäischen Recht der wirtschaftlichen Integration zu erreichen. Diese Lösungen müssen aber zugleich ausreichend differenziert sein, um die legitimen Unterschiede nationaler Wohlfahrtsregime zu respektieren. Dieses Working Paper beschäftigt sich mit zweien solcher Lösungsmöglichkeiten: Vertiefte Zusammenarbeit sowie eine Kombination differenzierter Rahmenrichtlinien mit der Offenen Methode der Koordinierung.
Keywords: 300